EXPANSION OF THE ASSORTMENT AND DEVELOPMENT OF TECHNOLOGY FOR INNOVATIVE SALAD DRESSINGS FOR THE RESTAURANT INDUSTRY - KUZMENKO, ROSTYSLAV; NEMIRIC, OLEKSANDRA; PAVLYUCHENKO, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The development of innovative salad dressings is closely connected with the growing consumer demand for healthy and functional products that combine high nutritional value with attractive sensory qualities. Modern gastronomic trends emphasize the use of natural ingredients, enriched with biologically active compounds, and the improvement of technological approaches aimed at obtaining stable and safe food products. One of the most effective ways of creating new dressings is the blending of vegetable oils, since this allows achieving a balanced fatty acid profile, increasing the antioxidant potential, and ensuring better organoleptic properties.In this study, a new innovative salad dressing named “Trytsillia” was developed in accordance with current tendencies in healthy nutrition. The recipe was based on a blend of olive, sea buckthorn, and hemp oils in the proportion of 60:20:20, which made it possible to optimize the ratio of omega-3 and omega-6 fatty acids, improve the biological value, and enrich the product with natural antioxidants and vitamins. The dressing was additionally supplemented with galangal root powder, oregano, and “Sriracha” sauce, which provided a characteristic spicy flavor, improved aroma, and expanded the functional properties of the product.The technological process included the preparation of raw materials, blending of oils, and the gradual incorporation of spices and seasonings, followed by homogenization to obtain a stable product. The developed dressing was analyzed using sensory evaluation, chromatographic analysis of aroma compounds, microscopic observation of emulsion stability, and assessment of its nutritional characteristics. The product demonstrated a uniform structure, pleasant appearance, balanced flavor, and a favorable nutritional profile enriched with valuable bioactive components.The results confirmed that the proposed formulation meets modern requirements for healthy and functional food products and has strong potential for application in the restaurant industry. The combination of blended vegetable oils with natural aromatic additives ensures not only improved nutritional value but also distinctive sensory properties and technological stability. The introduction of such products into the assortment of restaurants will expand the variety of menu items, support the principles of healthy nutrition, and increase the competitiveness of enterprises.
Keywords: salad dressing; oil blending; restaurant industry; sea buckthorn oil; olive oil; hemp oil; quality indicators